A numerical investigation of heat transfer and clogging in smooth and ribbed cooling channels of the GEF9’s first rotor blade - Tohid Moghimi; Seyyed Amirreza Abdollahi; Esmaeil Poursaeidi; Seyyed Faramarz Ranjbar (Results in Engineering)
Analysis of heat transfer and the possibility of clogging in gas turbines play a crucial role in their design and material selection. Due to the high operating temperatures of gas turbine blades, internal blade cooling is utilized to reduce the damage of high temperatures and enhance the durability of gas turbines. Among these methods, the blades' internal cooling is one of the most common approaches. The main objective of this research is to investigate the feasibility of using ribs to increase the internal cooling rate and consequently reduce the surface temperature of the second rotor blade of the GEF9 turbine. Additionally, the experimental observations of damaged blades, proved that some of the internal cooling paths are blocked due to particle deposition of dusty cooling air. So, the main innovation of this research lies in simulating the dust trajectory of dust particles within the cooling channels using an Eulerian-Lagrangian approach to predict blockages in the cooling channels, as well as investigating erosion resulting from the impact of dust particles with the cooling passage walls. Based on the obtained results, ribs increase the convective heat transfer up to 40 % but raise the pressure drop in other hands. With analysis of different types of geometrical parameters, the best thermal efficiency is about 0.76 (less than 1). The probability of clogging in the ribbed channels is 100 times more than smooth ones and also the rate of erosion in ribbed channels is 10 % more than smooth channels which can increase the stress and reduce the durability of the blade. So using rib in this type of blade is not feasible. By comparing the volume fractions of dust particles near the internal walls in the smooth cooling channels, the first and fourth channels have the highest and lowest likelihood of blockages, respectively and it shows that front channels should be designed with higher diameter.